2018
DOI: 10.1101/315168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipid composition but not curvature is a determinant of a low molecular mobility within HIV-1 lipid envelope

Abstract: Human Immunodeficiency Virus type-1 (HIV-1) acquires its lipid membrane from the plasma membrane of the infected cell from where it buds out. Previous studies have shown that the HIV-1 envelope is a very low mobility environment with the diffusion of incorporated proteins two orders of magnitude slower than in plasma membrane. One of the reasons for this difference is thought to be due to HIV-1 membrane composition that is characterised by a high degree of rigidity and lipid packing.To further refine the model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…on the scale of individual (< 140 nm) HIV-1 particles. For example, experiments employing a combination of super-resolution STED microscopy and fluorescence correlation spectroscopy (STED-FCS (10) or scanning STED-FCS, sSTED-FCS (11,12)) revealed a low mobility of molecules on HIV-1 surface (3) due to the high degree of lipid packing in the virus membrane (12,13). The retroviral protein Gag is thought to be a key player in altering the HIV-1 lipid environment as it is not only the main structural determinant of the particle assembly, but it also mediates interactions between assembling virus particle and plasma membrane lipids.…”
Section: Introductionmentioning
confidence: 99%
“…on the scale of individual (< 140 nm) HIV-1 particles. For example, experiments employing a combination of super-resolution STED microscopy and fluorescence correlation spectroscopy (STED-FCS (10) or scanning STED-FCS, sSTED-FCS (11,12)) revealed a low mobility of molecules on HIV-1 surface (3) due to the high degree of lipid packing in the virus membrane (12,13). The retroviral protein Gag is thought to be a key player in altering the HIV-1 lipid environment as it is not only the main structural determinant of the particle assembly, but it also mediates interactions between assembling virus particle and plasma membrane lipids.…”
Section: Introductionmentioning
confidence: 99%
“…How enveloped viruses acquire their lipid membrane shell is of great importance for their biogenesis and their capacity to infect cells. In the case of HIV-1, recently it has been shown that the envelope lipid composition was a determinant of low molecular mobility of the Env protein (3,13). Several works have been conducted to reveal different envelope viruses having their own unique lipid composition (2,4,6,36), implying their distinct biological requirements during infection, and suggesting their capacity in sorting specific host lipids into their virus membrane.…”
Section: Discussionmentioning
confidence: 99%